Once upon a Time...: Comments on the Myth of Female Dominance - Rogers, Susan Carol (Anthropologica, 2022)
The author shows how the articles in this special issue are representative of the new trends in women/gender studies. Reviewing the general orientations in that field for the last 25 years, she points out that more recent studies abandon broad generalizations on dominance attributed to human nature and emphasize more localized analyses of the distribution and use of power.